Basin of Mexico aquifer system: regional groundwater level dynamics and database development - Carrera-Hernández, J. J; Gaskin, S. J (Hydrogeology journal, 2007)
The aquifer system of the Basin of Mexico is the main source of water supply to the Mexico City Metropolitan Zone. Management of the Basin's water resources requires improved understanding of regional groundwater flow patterns, for which large amounts of data are required. The current study analyses the regional dynamics of the potentiometric groundwater level using a new database called the Basin of Mexico Hydrogeological Database (BMHDB). To foster the development of a regional view of the aquifer system, data on climatological, borehole and runoff variables are part of the BMHDB. The structure and development of the BMHDB are briefly explained and then the database is used to analyze the consequences of groundwater extraction on the aquifer's confinement conditions using lithology data. The regional analysis shows that the largest drawdown rates are located north of Mexico City, in Ecatepec (a region that has not yet received attention in hydrogeological studies), due to wells that were drilled as a temporary solution to Mexico City's water-supply problem. It is evident that the aquifer has changed from a confined to an unconfined condition in some areas, a factor that is responsible for the large subsidence rates (40 cm/year) in some regions.